Former Fortune 250 CEO Deanna Mulligan (Thirty Minute Mentors). - Mendler | Thirty Minute Mentors, Adam (linkedin.com, 2022)
Learn valuable lessons in strengths-based leadership with former Guardian Insurance CEO Deanna Mulligan, one of the most powerful women in business.